Proceeding international seminar Disaster: Theory, Research, and policy (The Graduate School of Gadjah Mada University October 20-22, 2009) - Sudibyakto, Dyah R. Hizbaron (Graduate School of Gadjah Mada University, 2009)
Proceeding international seminar Disaster: Theory, Research, and policy